Does prescribing of immediate release oxycodone by emergency medicine physicians result in persistence of Schedule 8 opioids following discharge?. (14th December 2019) - Veal, Felicity; Thompson, Angus; Halliday, Samuel; Boyles, Peter; Orlikowski, Chris; Huckerby, Emma; Bereznicki, Luke
Abstract: Objectives: To identify the prevalence of oxycodone immediate release (IR) prescribed during an ED admission and the persistence of Schedule 8 (S8) opioids following an ED admission. Methods: A retrospective cross‐sectional audit was undertaken reviewing all admission at the ED of the Royal Hobart Hospital, Tasmania, between 1 August and 30 September 2016. The admissions lists for ED were cross matched with the narcotic registers for oxycodone IR (the most commonly supplied S8 in ED) to identify how many patients received IR oxycodone during their ED admissions. Determination of the persistence of opioid use in opioid naïve patients was then undertaken using the Tasmanian real time reporting database of all S8 opioid dispensed in Tasmania (DAPIS). Results: There were 8432 ED admissions for 7065 patients aged over 13 years. IR oxycodone was prescribed during 1049 of these admissions (12.4%). Of the patients who were not taking regularly prescribed S8 opioids prior to their ED admission ( n = 853), 48 patients (5.6%) were taking S8 opioids at both 2 and 6 months following their ED admission. Thirty patients (2.8%) were approved for authorities for long‐term opioids for non‐cancer pain. Conclusion: These findings suggest that prescribing of IR oxycodone within ED is lower than previous studies. Additionally, the progression to regular chronic opioid use following an ED admission where IR oxycodone was given was relatively low with 3.0% of opioid naïve patients being approved for indications related to chronic non‐cancer pain in the following 6 months.